The Myth of Paris in the Russian Literature of the 18th Century - Колбасин, Вадим (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The myth of Paris, formed in the Russian literature of the 18th – early 19th centuries, is an expression of the mythological consciousness in which the ‘space – time’ dichotomy is cyclical: it is a myth of eternal return. This Parisian myth was based on a set of oppositions between the cultural and intellectual orientations in the two countries. The Russian consciousness was characterized by a sense of lack of liberty and by inclination for reflection and hesitation, whereas the enlightened France prided itself on the clarity and concreteness of its thinking and was highly aware of its pioneering role in the political and cultural world of its time. Therefore, the Russian Parisian myth was accompanied by the motifs of travel, escape, release – an ‘eternal return’ to a dream. Several generations of Russian writers, from Trediakovsky to Pushkin, impressed it on the mythological consciousness of their readers by establishing an image of Paris as a feast of life, as a city of exceptional power of expression.